Voting Up? The Effects of Democracy and Franchise Extension on Human Stature - Alberto Batinti; Joan Costa-Font; Timothy J. Hatton (Institute of Labor Economics (IZA), 2019)
We study the health effects of the spread of democratic institutions and the extension of voting rights in 15 European countries since the middle of the nineteenth century. We employ both cross country and cohort variation in heights and employ a new instrument for democracy and the extension of the franchise, the effect of decolonisation on democracy in the colonising country's democratisation to identify the causal effect of democracy on heights. We find robust evidence of a link between democratic quality and human stature. The results indicate that the transition to democracy increased average male heights by 0.7 to 1 cm, equivalent to a one-decade average increase in stature across cohorts. Including the extension of the franchise to women increases the effect on average stature to about 1.7cm. The effect is driven by both political participation and contestation in reducing inequality and expanding health insurance coverage.
Keywords: H1; J18; 330; voting rights expansions; transition; democracy; height; franchise